2018
DOI: 10.1111/cdoe.12440
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about managing dental problems among older people and dental professionals in Southern Brazil

Abstract: Objectives To explore the sociocultural context in which patients and dentists in urban and rural communities in Southern Brazil interpret dental problems. Method Beliefs and experiences related to dental problems were explored in eight focus groups involving a total of 41 older patients, and in direct interviews with two dentists and two dental assistants. The interactions were audio recorded and transcribed for thematic analysis. Results The beliefs and experiences of the participants focused on four main th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 32 publications
0
13
0
7
Order By: Relevance
“…29,30 In Brazil, these factors are conditioned by specific cultural aspects that vary in different regions of the country, depending on factors such as cultural traditions, social values and lifestyles. 30 Edentulism-the state of being toothless-is often seen as a normal part of everyday life within certain cultural contexts. 30 For example, in ancient cultural practice involved replacing natural teeth with complete dentures before marriage, as it was believed that pregnant women were not allowed to go to the dentist due to potential harm 30,31 Consequently, successive generations have come to understand it as natural, free of social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In Brazil, these factors are conditioned by specific cultural aspects that vary in different regions of the country, depending on factors such as cultural traditions, social values and lifestyles. 30 Edentulism-the state of being toothless-is often seen as a normal part of everyday life within certain cultural contexts. 30 For example, in ancient cultural practice involved replacing natural teeth with complete dentures before marriage, as it was believed that pregnant women were not allowed to go to the dentist due to potential harm 30,31 Consequently, successive generations have come to understand it as natural, free of social stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in terms of edentulism may be explained by the fact women use dental services more frequently 13 . This is particularly critical for older adults, for whom extraction of teeth and fabrication of dentures represented the only type of dental care available when they were younger 14 . This is somewhat different from the global estimates of oral disorders published by the GBD 2017 Oral Disorders Collaborators 15 , when no sex differences had been reported.…”
Section: Discussionmentioning
confidence: 99%
“…38,[41][42][43]46 Cultural beliefs, expectations regarding dental treatments and fatalism related to the inevitability of losing the natural dentition are likely to influence how edentulous older adults perceive the need to access dental services. 47 Goulart et al 48 reported that a group of older adults from the South of Brazil associated the use of prosthodontics with good oral health status. In contexts with limited access to preventive and restorative treatments and excessive barriers to navigating the health system, becoming edentulous is likely to be perceived as the only available option, as well as a manner to minimise dependence on dental services altogether.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%